The Implementation of English Instructional Design Based on Curriculum 2013 at Acceleration Program SMP N 1 Boyolali: Naturalistic Study - Kurniawati, Yoana, Muamaroh, Ph.D, Mauly Halwat Hikmat, Ph. D (2016)
Kurniawati, Yoana 2014. The Implementation of English instructional design (EID) based on curriculum 2013 at acceleration program SMP N 1 Boyolali: Naturalistic study.Thesis. Muhammadiyah University of Surakarta. The purpose of this study was to describe the instructional design in acceleration class which includes syllabus, learning objectives, instructional material, classroom procedure and class activities, teacher's and student's roles, media and evaluation. The instrument to get the data were: classroom observation and interview. This study used descriptive and qualitative research. This study found that (1) There are two learning objective of teaching English especially in English teaching namely: general objective and specific objective. (2) The type of syllabus used is notion functional syllabus.(3) Instructional materials are printed and unprinted material (4) The implementation of the classroom procedure applied in the study was adapted from the PPP theory (Presentation, practice and procedure). (5) Theteacher's role isas a facilitator, a group organizer and an explainer. The learner's role is as a performer, and a listener. The student's roles is learners plan his/ her own learning program and this ultimately assumes responsibility for what they do in the classroom, group and learn by interacting with others, learner tutor other learners, (6) The media used in teaching learning process laptop and LCD (7) Evaluation model used are formative and summative. (8) The obstacle faced by the teacher of the student are the students' competency are not the same they have different level in their achievement, and the system of scoring. (9) The solution taken by the teacher to solve the problems is by giving the motivation for the lower group and for the limited timing Key words: Instructional design, Curriculum 2013, Acceleration program.